Effect of minerals on the stability of gold in copper ammoniacal thiosulfate solutions - The role of copper, silver and polythionates - Staunton, William; Aylmore, M.; Muir, D. (Elsevier Science BV, 2014)
The effect of some typical oxide and sulide minerals, as well as activated carbon, on synthetic gold thiosulfate leach solutions was examined. The presences of pyrite and goethite in a synthetic ore slurry have a significant effect on the adsorption and stability of gold, silver, copper and polythionates in ammoniacal thiosulfate solutions. Adsorption of tetrathionate in particular leads to significant gold and silver losses. The adsorption of copper on mineral surfaces inhibited gold and silver losses, even in the presence of tetrathionate. However, goethite was found to strongly adsorb copper(II). It is concluded that gold extraction from natural ores is lower than that obtained with cyanide, partly as a result of sorption or precipitation reactions. Furthermore, the presence of silver in solution catalyses the precipitation of a mixed copper/silver/gold sulfide in ammoniacal thiosulfate solutions containing tetrathionate.